Protective effect of low-intensity treadmill exercise against acetylcholine-calcium chloride-induced atrial fibrillation in mice - 성동준(Dong-Jun Sung), 전용균(Yong-Kyun Jeon), 최재일(Jaeil Choi), 김보경(Bokyung Kim), Shadi Golpasandi(Shadi Golpasandi), 박상웅(Sang Woong Park), 오승범(Seung-Bum Oh), 배영민(Young Min Bae) (The Korean journal of physiology & pharmacology, 2022)
Atrial fibrillation (AF) is the most common supraventricular arrhythmia, and it corresponds highly with exercise intensity. Here, we induced AF in mice using acetylcholine (ACh)-CaCl2 for 7 days and aimed to determine the appropriate exercise intensity (no, low, moderate, high) to protect against AF by running the mice at different intensities for 4 weeks before the AF induction by ACh-CaCl2. We examined the AF-induced atrial remodeling using electrocardiogram, patch-clamp, and immunohistochemistry. After the AF induction, heart rate, % increase of heart rate, and heart weight/body weight ratio were significantly higher in all the four AF groups than in the normal control; highest in the high-ex AF and lowest in the low-ex (lower than the no-ex AF), which indicates that low-ex treated the AF. Consistent with these changes, G protein-gated inwardly rectifying K+ currents, which were induced by ACh, increased in an exercise intensity-dependent manner and were lower in the low-ex AF than the no-ex AF. The peak level of Ca2+ current (at 0 mV) increased also in an exercise intensity-dependent manner and the inactivation time constants were shorter in all AF groups except for the low-ex AF group, in which the time constant was similar to that of the control. Finally, action potential duration was shorter in all the four AF groups than in the normal control; shortest in the high-ex AF and longest in the low-ex AF. Taken together, we conclude that low-intensity exercise protects the heart from AF, whereas high-intensity exercise might exacerbate AF.